Reviews (Modern theology, 1987)
Book reviewed in this article: Stephen Sykes: The Identity of Christianity: Theologians and the Essence of Christianity from Schleiermacher to Barth. Form and Vitality in the World and God: A Christian Perspective. By Trevor Williams Marc H. Ellis, Toward A Jewish Theology of Liberation Theology, Church and Ministry, by John Macquarrie THE AUTHORITY OF A BISHOP by John Halliburton